1994
DOI: 10.1007/bf01715499
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of hepatitis C in turkey

Abstract: Hepatitis C virus (HCV) and hepatitis E virus (HEV) are the principal causes of non-A, non-B hepatitis worldwide, and in Turkey one-third of the cases of acute hepatitis are non-A, non-B. To explore the epidemiology of HCV in Turkey (including the association of HCV with HEV), a seroprevalence study of HCV was conducted. Sera from residents from five distinct regions of the country were tested for antibodies to HCV (anti-HCV) and HEV (anti-HEV). Anti-HCV was detected in 21 (1.5%) of 1,374 persons and was more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
13
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
4
13
3
Order By: Relevance
“…anti-HBs (31.9%) seroprevalence fall within the ranges provided for countries with an intermediate endemic profile (4,20) and in agreement with past studies on epidemiology of hepatitis in Turkey which indicated an overall prevalence of chronic HBV infection of 4-10 % (3.5% in the western and 7% in the eastern regions), and of anti-HBs positivity of 20.6-52.3% [7,10,14,15,19,21,22]. This regional difference in HBV positivity, not observed in HCV infection, re-emphasizes the role of close contact and intrafamilial transmission in areas with crowded families and poor hygienic conditions in HBV seroprevalence.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…anti-HBs (31.9%) seroprevalence fall within the ranges provided for countries with an intermediate endemic profile (4,20) and in agreement with past studies on epidemiology of hepatitis in Turkey which indicated an overall prevalence of chronic HBV infection of 4-10 % (3.5% in the western and 7% in the eastern regions), and of anti-HBs positivity of 20.6-52.3% [7,10,14,15,19,21,22]. This regional difference in HBV positivity, not observed in HCV infection, re-emphasizes the role of close contact and intrafamilial transmission in areas with crowded families and poor hygienic conditions in HBV seroprevalence.…”
Section: Discussionsupporting
confidence: 86%
“…There is no national screening or reporting system for HCV in Turkey, and the epidemiological data are derived mainly from local studies [7,[12][13][14] indicating anti-HCV positivity from 0.4 to 1.5% in community-based studies, from 0.19 to 0.68%, in blood donors, 2.2 to 2.4% in patients during routine outpatient visits. The current best estimate for the prevalence was reported to be approximately 1% [1].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio was considerably higher than that reported in our general population which is 1.5% [5]. While 3 of the 4 HD patients whose partners were found to be anti-HCV positive were HCV-RNA positive, the last one was negative.…”
contrasting
confidence: 51%
“…Human MAVS was found as susceptible to cleavage by these non-human viral proteases, indicating that it does not pose a barrier for zoonotic transmission to humans (326). In Turkey, the seropositivity of HCV was detected as 1.5% in sera collected from 1374 people who live in five distinct regions of the country (327). Once a human is infected, the sparganum (plerocercoid) migrates to various tissues and organs, such as brain and eyes.…”
Section: Potential Zoonotic Viral Infections Groupmentioning
confidence: 99%